University and the debate of new humanities - Carvajal, Iván (2018)
The absence of places for research and the training of researchers in fundamental areas such as anthropology, history, linguistics and, all in all, philosophy has had a negative impact on the country. There has been room for the social sciences, although subordinated to other disciplines, such as law, but not for the humanities, which have been denied their place, subordinating them. If it is desired to promote Ecuadorian higher education, it is necessary that the Central University, because of its history, its location in the capital of the country, because of its links with society, is the place where the objectives of transformations are proposed and strengthened Democratic institutions of the university institution. In this age of devastation, neo-fascism, hypertechnological capitalism, there is a call for courage to open minds, courage to think without ideological or moral obstacles, courage for criticism, for deconstruction, for debate, for To establish consensus but also to defend the University as an area for difference and dissent.